Evaluation of the Diagnosis of Typhoid Fever Using the Widal Test and the Anti Salmonella typhi IgM Test - Wahdah Norsiah; Neni Oktiyani (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2020)
Typhoid fever is a systemic infectious disease caused by Salmonella enteric serotype typhi. Laboratory tests are essential because the clinical symptoms of typhoid fever are not specific. The definitive diagnosis of typhoid fever make by culture isolation of Salmonella typhi, but this test is expensive and takes a long time. Other supporting tests that can do quickly are the Widal and Salmonella typhi IgM tests. This study aimed to determine the suitability between the results of the Widal test and the results of the anti-Salmonella typhi IgM test. This type of research is an observational analytic study determining the sample based on the accidental sampling technique. The number of samples taken was 42 samples. The results showed that the Widal Test in typhoid patients was 76% positive and 24% negative. Based on the anti-Salmonella typhi IgM test results in typhoid patients, 38% were positive, and 62% were negative. The study concluded a fragile agreement between the Widal test results and the results of the anti-Salmonella typhi IgM test. It recommended that the Widal test carried out for the initial examination and a quick community survey. The Tubex test highly recommends for diagnosis.